Legal Psychological Literacy In The Family (Zien Journal of Social Sciences and Humanities, 2022)
Psychology is the science of mental reflection of reality, mental processes, situations, events, feelings in the process of human activity and animal behavior. The research subject of psychology includes such psychological processes and categories as sensations and images of perception, thinking and feeling, activity and behavior. The main tasks of psychology are to reveal the laws of the psyche, the formation of human mental states in the unity of phylogenetic and ontogenetic development. In finding a solution to these tasks, on the one hand, psychology is in close contact with the fields of biological science, including physiology, and on the other hand, with sociology, pedagogy, cultural history, logic, and social sciences. Psychology is primarily the study of consciousness and self-awareness, which is the human form of psyche.